Residential energy use and the relevance of changes in household circumstances - Simonetta Longhi (University of Essex, Institute for Social and Economic Research (ISER), 2014)
We use a panel of UK households to analyse the impact that various individual, household and dwelling characteristics have on energy expenditures and whether changes in household socio-economic circumstances translate in changes in energy expenditures. Socio-economic characteristics have a moderate impact on per-capita energy expenditures, while dwelling characteristics and especially household size have much larger impacts in magnitude. Similarly, the largest changes in energy expenditures are related to changes in household size rather than to changes in other socio-economic and dwelling characteristics. The recent socio-demographic trends will make it harder to design policies to effectively reduce the carbon footprint of a country, while policies influencing cohabitation and family size may have positive indirect effects.
Keywords: D12; Q41; 330; Energy expenditures; households; longitudinal analysis; UK